Discriminating trait-convergence and trait-divergence assembly patterns in ecological community gradients - Pillar, Valério D.; Duarte, Leandro da S.; Sosinski, Enio E.; Joner, Fernando (Journal of vegetation science, 2009)
Question: Whereas similar ecological requirements lead to trait-convergence assembly patterns (TCAP) of species in communities, the interactions controlling how species associate produce trait-divergence assembly patterns (TDAP). Yet, the linking of the latter to community processes has so far only been suggested. We offer a method to elucidate TCAP and TDAP in ecological community gradients that will help fill this gap. Method: We evaluated the correlation between trait-based described communities and ecological gradients, and using partial correlation, we separated the fractions reflecting TCAP and TDAP. The required input data matrices describe operational taxonomic units (OTUs) by traits, communities by the quantities or presence-absence of these OTUs, and community sites by ecological variables. We defined plant functional types (PFTs) or species as community components after fuzzy weighting by the traits. The measured correlations for TCAP and TDAP were tested by permutation. The null model for TDAP preserves the trait convergence, the structure intrinsic in the fuzzy types, and community total abundances and autocorrelation. Results: We applied the method to trait-based data from plant communities in south Brazil, one set in natural grassland experimental plots under different nitrogen and grazing levels, and another in sapling communities colonizing Araucaria forest patches of increasing size in a forest-grassland mosaic. In these cases, depending on the traits considered, we found strong evidence of either TCAP or TDAP, or both, that was related to the environmental gradients. Conclusions: The method developed is able to reveal TCAP and TDAP that are more likely to be functional for specified ecological gradients, allowing establishment of objective hypotheses on their links to community processes.